Quantum Mechanics (QM) and Psychology: A New Field of Cooperation? - Giacomuzzi, Salvatore (Psychological Counseling and Psychotherapy, 2020)
We will try to present critically published works on Quantum Mechanics (QM) and Psychology (perhaps more generally regarding the so called social sciences), partly by ourselves (Giacomuzzi, 2008, 2002), in an overview. It is of course impossible to give a complete summary here, but critical points should be emphasized, which perhaps leave a more differentiated view on the problems of "psychological reality". Nowadays QM is “hip” in scientific literature. But common approaches doesn`t take into consideration that physicists already 80 years ago tried to establish a connection between life sciences and physics. But do neuroscientific findings really validate essential psychological basic assumptions? Do they really open up new, interdisciplinary research perspectives? Physics itself today struggles with its theories and we`ve a big gap between on what we experience and on what we really understand. Maybe this gap of understanding our own reality is much bigger than 120 years ago when QM was born by the work of Max Planck